KL double core hole pre-edge states of HCl. Issue 4 (11th January 2018) - Koulentianos, D.; Püttner, R.; Goldsztejn, G.; Marchenko, T.; Travnikova, O.; Journel, L.; Guillemin, R.; Céolin, D.; Piancastelli, M. N.; Simon, M.; Feifel, R.
Abstract : The formation of double core hole pre-edge states of the form 1s −1 2p −1 ( 1, 3 P)σ*, n  for HCl, located on the binding energy scale as deep as 3 keV, has been investigated by means of a high resolution single channel electron spectroscopy technique recently developed for the hard X-ray region. Abstract : The formation of double core hole pre-edge states of the form 1s −1 2p −1 ( 1, 3 P)σ*, n  for HCl, located on the binding energy scale as deep as 3 keV, has been investigated by means of a high resolution single channel electron spectroscopy technique recently developed for the hard X-ray region. A detailed spectroscopic assignment is performed based on ab initio quantum chemical calculations and by using a sophisticated fit model comprising regular Rydberg series. Quantum defects for the different Rydberg series are extracted and the energies for the associated double core hole ionization continua are extrapolated. Dynamical information such as the lifetime width of these double-core-hole pre-edge states and the slope of the related dissociative potential energy curves are also obtained. In addition, 1s −1 2p −1 V −1 n  λn ′′ λ ′ double shake-up transitions and double core hole states of the form 1s −1 2s −1 ( 1, 3 S)σ*, 4s are observed.